Vertical vibrations effect on forced convection heat transfer from a longitudinal finned tube - Kadhim, Saleem Khalefa; Ali, Sinan Abdulghafar; Razak, N. F. D.; M. S. M., Sani (IOP Publishing, 2021)
Thermal systems more efficient by emanating from industrial applications and space program galvanized interest in ways by increasing heat transfer is the system. The main aim of this paper is to investigate experimentally the effects of the vertical vibration and force convection on the average Nusselt number in a longitudinal finned tube. The finned tube was located inclined or horizontally in different angles of 0°, 30° and 45°. The effect of the excitation frequency covers below 16 Hz with various heat fluxes ranged from 500-1500 W/m2. It was noticed that the good agreement between the experimental measurement and the previous experimental studies with deviation of 5%. The results showed that average Nusselt number values at angle 45° from longitudinal finned tube were higher by up to 14%, 16% compared with the angles 30°, and 0°, respectively. Furthermore, it can be summarized that the vertical vibration significantly affects to the average Nusselt number from longitudinal finned tube cylinder and the influence on the heat transfer coefficient for this system should be considered.